Effect of Sn element on optimizing thermoelectric performance of Te nanowires. Issue 12 (24th September 2018) - Sun, Pengliang; Li, Changcun; Xu, Jingkun; Jiang, Qinglin; Wang, Wenfang; Liu, Jing; Zhao, Feng; Ding, Yongbo; Hou, Jian; Jiang, Fengxing
Abstract : The power factor of low dimensional Te NWs films was significantly increased by the lead-free metal Sn element. Abstract : Metal doping with inorganic materials has been considered an effective method used to improve thermoelectric (TE) performance. More specifically, recent efforts have focused on low-dimensional tellurium nanowires (Te NWs). Owing to the poor environmental stability and electrical conductivity of Te NWs, the optimization of TE performance for Te nanomaterials by metal-doping has gained great attention. In this work, tin (Sn), a typical non-lead metal element, was employed as a doping element to improve the TE performance of Te NWs. The influence of Sn on the TE performance of Te NWs was systematically investigated with different Sn contents. Results demonstrated that a 0.125 Sn/Te atom ratio after annealing with a high Seebeck coefficient of 400 μV K −1 achieved a maximum electrical conductivity for SnTe NWs films at approximately 600 S cm −1 . The Sn-doped Te NW (Sn0.125 Te) film presented a high power factor of 114.6 μW m −1 K −2, which was about two orders of magnitude higher than that of Te NWs film. This work highlights Sn-doping as an effective means to improve the TE performance of Te NWs.